Respostas
respondido por:
0
a=5; b=-6; c=-1
x= -b+/- √b^(2)-4*a*c
----------------
2*a
x=6+/- √36+20
-----------
10
x=6+/- √56
--------
10
x=6+/-2 √14
---------
10
x'=6+2 √14 3+ √14
-------- = ------
10 5
x"=6-2√14 3-√14
-------- = ------
10 5
x= -b+/- √b^(2)-4*a*c
----------------
2*a
x=6+/- √36+20
-----------
10
x=6+/- √56
--------
10
x=6+/-2 √14
---------
10
x'=6+2 √14 3+ √14
-------- = ------
10 5
x"=6-2√14 3-√14
-------- = ------
10 5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás